An Islamic Perspective on Organizational Motivation (American Journal of Islam and Society, 1995)
Organizations are an indispensable part of our lives, for they provideservices for satisfying our basic needs. Central to any organization's performanceis the motivation of its members. Indeed, organizational motivationis related closely to some fundamental questions in organizationtheory in particular and to public administration in general. Such questionsfocus on how organizations can be made efficient and responsiveor accountable to their clients. Since organizations are simply humancollectivities, in essence these questions apply to organizational membersand, in particular, to what motivates them to be efficient and responsive.Although various models of organization have addressed, eitherimplicitly or explicitly, the question of motivation in organizations, theyhave yet to come up with satisfactory answers. The significance of organizationalmotivation does not consist of its close relationship to the fundamentalquestions of organizational efficiency and responsiveness alone,but also of its relevance to how organizations are structured. As this latterconsideration may affect such concepts as human dignity, freedom,respect, brotherhood, and justice, this is tantamount to saying that organizationalstructures are not morally or spiritually neutral, inasmuch as thesevalues have moral and spiritual roots.Organizational structures are founded on certain underlyingassumptions about human nature and motivation that underpin severalprincipal organization models. One common characteristic of thesemodels is the assumption that the individual has certain self-centeredneeds that govern his/her behavior and that the organization can, by satisfyingthese needs, motivate the individual to contribute towards the ...